An Economic Analysis Of Government Custom Hiring Services For Different Farm Machineries In Bhutan - Kinga, N; Chetem, W (SAARC Journal of Agriculture, 2020)
Farmers in Bhutan trend to own agricultural machineries though the individual area under farm mechanization is not enough. Hiring out or in of farm machineries as a business enterprise need to be advocated. Therefore, an effort was made in this study to generate some parameters regarding farm machinery business at farm level based on practical experience. Bhutanese Government has endorsed some users’ parameters including cost and return which are used to guide the custom rates for different machineries for farmers and service providers. The study’s objective was to generate different empirical formula for different farm machineries which shall help to propose varying custom hiring rates based on the projected operation days based on the government endorsed parameters. It is also to ascertain whether the present rates charged by Farm Machinery Corporation Limited bring a positive return to its custom hiring business for different machines. The study revealed that the operation cost of farm machinery includes both fixed cost and variable cost. Cost, return and break-even data for different farm machineries give a confident opinion for the owners and Farm Machinery Corporation Limited (FMCL) to take up the hiring scheme as a profitable business. The custom hiring rate also gives a good guide on the custom hiring rates to be charged based on the operating days in the country. On endorsed hiring rates and parameters by government, FMCL shall be able to make a huge profit annually especially on tractors and mini combine harvesters as compared to other machineries by Nu 0.51M and 0.39 M respectively. All other machines are also making a profit annually under the government endorsed parameters. However, there is also an opportunity to reduce the custom rates to bring down the overall cost of cultivation of respective crops using the machines. SAARC J. Agri., 17(2): 93-101 (2019)